Pengaruh Market Orientation terhadap Kinerja UKM Art Market dengan Innovation Capability sebagai Variabel Mediasi - Nasihatul Fadhilah; Damelina Basauli Tambunan (Journal of Economics and Management Scienties, 2026)
This study aims to analyze the effect of Market Orientation (MO) on Innovation Capability (IC) and Business Performance (BP) in Art Market SMEs, as well as to examine the mediating role of IC in this relationship. The phenomenon underlying this study is the tendency of creative SMEs to rely on innovation driven by intrinsic factors such as passion, while paying less attention to market needs amid rapidly evolving global dynamics. This condition causes innovation to not necessarily generate an optimal impact on business performance. This study employs a quantitative approach using a survey method targeting SME actors or tenants participating in OMO Market Vol. 6 in Jakarta. Data analysis was conducted using Structural Equation Modelling (SEM) with SmartPLS software. The results show that Market Orientation has a positive and highly significant effect on Innovation Capability, with a path coefficient of 0.771, positioning it as a primary driver of innovation. Furthermore, Innovation Capability is proven to be the main driver of Business Performance, with a coefficient of 0.505. Another key finding indicates that the direct effect of Market Orientation on Business Performance is relatively lower (0.327) compared to its indirect effect through the mediation of Innovation Capability (0.390). In conclusion, Innovation Capability is a key factor that directly enhances the performance of creative SMEs. However, to achieve more optimal and sustainable performance, innovation capability must be grounded in market orientation to remain aligned with market dynamics.